Pengaruh Karakteristik Dewan Direksi dan Dewan Komisaris terhadap Restatement - Vivian Linardi; Belinda Belinda; Sany Sany (Business Accounting Review, 2021)
This study aims to determine the effect of board characteristics which include number of the Boardof Director (BOD), the presence of women on BOD, independent Board of Commissioner (BOC) andCEO overconfidence in restatement. The independent variables were the number of the BOD, thepresence of women on BOD and CEO overconfidence were measured by nominal scale, independentBOC is measured by ratio scale. The dependent variable is restatement which is measured bydummy variable. The sample used is 132 observations from financial companies listed on theIndonesia Stock Exchange for the period 2015 to 2020. The data used are obtained from thecompany's annual reports and Bloomberg. The analytical technique is logistic regression. The resultsof the study conclude the number of BOD and independent BOC has no effect on the occurrence ofrestatements. However, the presence of women on BOD has a significant negative and CEOoverconfidence has a significant positive effect on the occurrence of restatements.